Social and Occupational Changes in Small Towns in The Swiętokrzyskie Voivodship During the Transformation of the Political System - Mularczyk Mirosław (Miscellanea Geographica: Regional Studies on Development, 2006)
The objective of the paper is to present social and occupational changes in small towns in the Świętokrzyskie Voivodship in regard to their accessibility to communication with larger towns in the examined area. Because of the availability of statistic data for the analysis, the time period from 1995 to 2004 was selected.